Polarized sources, targets and polarimetry : proceedings of the 13th International Workshop, Ferrara, Italy, 7 - 11 September 2009 - Ciullo, G.; Contalbrigo, M.; Lenisa, P. (New Jersey : World Scientific Publishing, 2011)
Includes bibliographical references and index